Non-operative treatment of acute appendicitis in selected patients - Agaoglu, Nazim; Ulusahin, Mehmet (International Surgery Journal, 2017)
Background: Surgical approach for acute appendicitis (AA) is a standard live saving treatment method. The purpose of this study was to assess the feasibility, initial safety and success rate of non-operative treatment of AA in selected patients. Methods: Selected AA patients were enrolled in this prospective study (non-operative treatment). This was based on IV antibiotic therapy and followed up with oral antibiotic. Patients who declined to participate or excluded were managed with appendectomy and considered as controls. The primary goal of the study was to determine the feasibility, initial safety, early and late success rates of non-operative management. Secondary outcomes include hospital length of stay and charge, days of missed works and return to normal activity at home of patients treated non-operatively in comparison to appendectomy group. Results: In non-operative group (36 patients), 7 patients failed to response and managed by appendectomy with early success rate of 80.5%. Three patients experienced recurrent attacks of AA were managed with appendectomy. Late success rate was 72.2%. In appendectomy group (53 patients) one patient with adenocarcinoma of the colon detected during surgery and in ten patients the appendix was perforated. One patient died due to generalized peritonitis. In non-operative group length of stay and hospital charge were lower but only days to resume home activities and days of missed work were shorter and statistically significant as compared to appendectomy group. Conclusions: This study confirms the feasibility, safety and optimum success rate of non-operative treatment of early AA in selected patients.